Liquid crystal polyimide aerogel with excellent shape memory performance and preparation method thereof

By using copolymerization reaction and directional frozen casting in polyimide aerogels, liquid crystal polyimide aerogels with excellent shape memory performance are prepared, which solves the problems of low thermal conductivity and slow shape recovery rate in the prior art, and achieves fast thermal response and stable shape memory at high temperatures.

CN119529369AActive Publication Date: 2025-02-28JIANGNAN UNIV

Patent Information

Application Number
CN202411645280.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-18
Publication Date
2025-02-28
Estimated Expiration
2044-11-18

AI Technical Summary

Technical Problem

Existing shape memory polyimide aerogels show low thermal conductivity and slow shape recovery rate in high temperature scenarios, which cannot meet the needs of high temperature fields such as aerospace.

Method used

By copolymerizing liquid crystal diamine, flexible diamine and liquid crystal dianhydride monomer in polyimide aerogel, adding a heat curing agent, and using directed frozen casting and thermal imidation processes, a liquid crystal polyimide aerogel with excellent shape memory performance was prepared.

Benefits of technology

It improves the thermal conductivity and shape memory performance of liquid crystal polyimide aerogel, achieves rapid thermal response and stable shape memory at high temperatures, and expands its application in aerospace and other high temperature fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119529369A_ABST
    Figure CN119529369A_ABST
Patent Text Reader

Abstract

The invention discloses liquid crystal polyimide aerogel with excellent shape memory performance and a preparation method of the liquid crystal polyimide aerogel, and belongs to the field of polymer aerogel materials. According to the liquid crystal polyimide aerogel with the excellent shape memory performance, the shape fixing rate is larger than or equal to 99%, and the shape recovery rate is larger than or equal to 97%; the heat conductivity at the room temperature is larger than or equal to 0.09 W m <-1 > K <-1 >; specifically, liquid crystal diamine, flexible diamine, a liquid crystal dianhydride monomer and a thermal curing agent are subjected to a reaction and solvent replacement, and polyamide acid dry filaments are obtained; and forming an aqueous solution from the dry polyamide acid filaments, injecting the aqueous solution into a silica gel mold, carrying out directional freezing casting on a customized freezing circulating device with a copper plate at the top, and carrying out freeze drying, thermal imidization and curing after molding, so as to obtain the liquid crystal polyimide aerogel with excellent shape memory performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a liquid crystal polyimide aerogel with excellent shape memory performance and a preparation method thereof, and belongs to the field of polymer aerogel materials. Background Art

[0002] Shape memory polymer aerogel with high porosity is a new type of special material with ultra-low density. It combines the unique properties of aerogel (such as ultra-low density, high specific surface area and porosity) with the highlights of polymer in shape memory, so it has many application prospects in the fields of sensors, bionic structures, and deployable panels. However, people's research on shape memory polymer aerogels is mainly focused on materials such as polyurethane, polycaprolactone, and nanocellulose. The shape memory aerogels prepared from these materials have problems such as poor mechanical properties and low transition temperature (less than 120°C), which cannot meet the needs of aerospace or other high-temperature scenarios.

[0003] Polyimide is one of the organic polymer materials with the best comprehensive performance. It has excellent thermal stability, high temperature resistance of more than 400°C, long-term use temperature range of -200 to 300°C, and excellent mechanical properties. The most important thing is that its rigid structure makes its T g Generally higher than 200°C. Therefore, the use of polyimide to prepare shape memory aerogel is expected to expand the application of shape memory polymer aerogel in aerospace and other high-temperature fields.

[0004] Aerogel materials made of polyimide have the advantages of light weight, high strength, strong molecular designability, and low dielectric constant. However, polyimide aerogel is a high-porosity thermal insulation material with low thermal conductivity, which is inconsistent with the rapid thermal response of shape memory. If the thermal conductivity of polyimide aerogel can be appropriately improved, the contradiction of slow response rate caused by slow heat transfer in the polyimide aerogel skeleton can be alleviated, and then polyimide aerogel with shape memory properties can be prepared, promoting the application of polyimide aerogel in space intelligent structures.

[0005] Currently, the main way to improve the thermal conductivity of polyimide-based materials is to prepare polyimide-based thermal conductive composite materials by filling them with thermal conductive materials. This method usually requires adding a large amount of thermal conductive fillers to obtain the ideal thermal conductivity coefficient, which inevitably leads to a decrease in mechanical and processing properties, which limits its wider application. Summary of the invention

[0006] [Technical issues]

[0007] The existing shape memory polyimide aerogels mainly include polyimide-based composite aerogels and pure polyimide aerogels. The polyimide-based composite aerogels are mainly made by filling a large amount of fillers in the polyimide aerogels, and their thermal conductivity is significantly improved, but the shape memory performance still has a lot of room for improvement. The pure polyimide aerogels reported are mainly made by designing the molecular structure of polyimide aerogels, and their shape memory performance is relatively excellent, but their thermal conductivity is not significantly improved, and the shape recovery rate is low.

[0008] [Technical solution]

[0009] In view of the defects and shortcomings of the prior art, the purpose of the present invention is to improve the thermal conductivity of shape memory polyimide aerogel, balance the contradiction between the low thermal conductivity of polyimide aerogel and the rapid thermal response required for shape memory; at the same time, improve the problem of poor shape memory performance of polyimide aerogel, and then prepare a polyimide aerogel material with excellent shape memory performance, and promote the application of polyimide aerogel materials in the field of lightweight intelligent deformation materials.

[0010] Specifically, liquid crystal diamine, flexible diamine and liquid crystal dianhydride monomers are copolymerized, and a thermal curing agent is added after the reaction to continue the reaction to obtain a polyamic acid solution; the polyamic acid solution is solvent replaced in ultrapure water, and polyamic acid dry fibers are obtained after freezing and drying; the polyamic acid dry fibers are then formulated with triethylamine into a polyamic acid aqueous solution, the polyamic acid aqueous solution is injected into a silicone mold, and directionally freeze-casted on a customized freezing cycle device with a copper plate on the top, and after molding, freeze-dried, thermally imidized and cured to obtain a liquid crystal polyimide aerogel with excellent shape memory properties.

[0011] In order to achieve the above object, the present invention adopts the following technical solution:

[0012] The first object of the present invention is to provide a liquid crystal polyimide aerogel with excellent shape memory properties, wherein the shape fixation rate of the liquid crystal polyimide aerogel is ≥99%, the shape recovery rate is ≥97% and the thermal conductivity at room temperature is ≥0.09Wm -1 K -1 .

[0013] The second object of the present invention is to provide a method for preparing a liquid crystal polyimide aerogel having excellent shape memory properties, the method comprising the following steps:

[0014] (1) subjecting a liquid crystal diamine, a flexible diamine monomer and a liquid crystal dianhydride monomer to a condensation polymerization reaction in N-methylpyrrolidone (NMP), adding a thermal curing agent after the reaction, and continuing the reaction to obtain a polyamic acid solution; subjecting the polyamic acid solution to solvent replacement, and then freezing and freeze-drying to obtain polyamic acid dry fibers;

[0015] (2) adding the polyamic acid dry silk obtained in step (1) and triethylamine into ultrapure water, heating and stirring evenly to obtain a polyamic acid aqueous solution;

[0016] (3) injecting the polyamic acid aqueous solution obtained in step (2) into a silica gel mold, and placing the mold on a customized refrigeration cycle device with a copper plate on the top for directional freeze casting, and placing it in a freeze dryer for freeze drying after molding to obtain a polyamic acid aerogel;

[0017] (4) The polyamic acid aerogel obtained in step (3) is subjected to thermal imidization and thermal curing to obtain a liquid crystal polyimide aerogel, that is, a liquid crystal polyimide aerogel with excellent shape memory properties.

[0018] In one embodiment, the liquid crystal diamine monomer in step (1) is one or both of 1,3-bis(4-aminophenoxy)benzene (TPE-R) and 1,4-bis(4-aminophenoxy)benzene (TPE-Q).

[0019] In one embodiment, the flexible diamine monomer in step (1) is 1,3-bis(3-aminophenoxy)benzene (TPE-M).

[0020] In one embodiment, the liquid crystal dianhydride monomer in step (1) is 4,4'-phenylenedioxydiphthalic anhydride (HQDPA).

[0021] In one embodiment, the heat curing machine in step (1) is one or two of 4-ethynylaniline (4-EA) and nadic anhydride (NA).

[0022] In one embodiment, the molar ratio of the liquid crystal diamine monomer to the flexible diamine monomer in step (1) is 1:(0-1), and the molar ratio of the liquid crystal diamine monomer to the liquid crystal dianhydride monomer is 1:(0.95-2.5), preferably 1:(2.01-2.20).

[0023] In one embodiment, the molar ratio of the liquid crystal diamine to the thermal curing agent in step (1) is 1:(0-0.1), preferably 1:0.06.

[0024] In one embodiment, the polycondensation reaction in step (1) is carried out in an ice-water bath for 12-18 hours.

[0025] In one embodiment, the reaction time after adding the thermal curing agent in step (1) is 3-6 hours.

[0026] In one embodiment, the solid content of the polyamic acid solution in step (1) is 10-20 wt %.

[0027] In one embodiment, the solvent replacement time in step (1) is 0.5-2h.

[0028] In one embodiment, the heating stirring speed in step (2) is 500-1000 rpm, the temperature is 36-42° C., and the time is 0.5 h-3 h.

[0029] In one embodiment, the concentration of polyamic acid in the polyamic acid aqueous solution in step (2) is 100-120 mg / ml.

[0030] In one embodiment, the customized refrigeration cycle device with a copper plate on the top in step (3) is specifically a cubic box with a copper plate on the top and a layer of thermal insulation material around it, and the box contains anhydrous ethanol at -40°C to 100°C.

[0031] In one embodiment, the temperature of the directional freeze casting in step (3) is -120 to -20°C, and the time is 1 to 24 hours.

[0032] In one embodiment, the temperature of the freeze dryer in step (3) is -80 to -20°C and the time is 48 to 96 hours.

[0033] In one embodiment, the temperature of the thermal imidization in step (4) is 25-350° C. and the time is 0.5 to 3 hours.

[0034] In one embodiment, the thermal curing temperature in step (4) is 270-330°C.

[0035] In one embodiment, the thermal imidization and thermal curing in step (4) can be carried out at the following temperature: 100-150°C for 0.5-1.5 hours, 200-250°C for 0.5-1.5 hours, and 270-330°C for 0.5-1.5 hours.

[0036] In one embodiment, the thermal imidization and thermal curing in step (4) need to be carried out under an inert atmosphere.

[0037] In one embodiment of the present invention, the equipment for high temperature heat treatment in step (4) is a tubular furnace, and the treatment is carried out under a nitrogen atmosphere.

[0038] The third object of the present invention is to provide the application of the above-mentioned liquid crystal polyimide aerogel with excellent shape memory properties in thermal insulation materials, aerospace vehicles, deployable panels, lightweight intelligent deformation materials, etc.

[0039] Compared with the prior art, the present invention has the following beneficial effects:

[0040] (1) The present invention prepares liquid crystal polyimide aerogel with excellent shape memory properties for the first time. The preparation method is relatively simple and environmentally friendly, with low cost and good formability. The aerogel structure is relatively stable and can be designed into various shapes, which can be suitable for use in a variety of extreme environments.

[0041] (2) The present invention utilizes a directional freezing strategy to cast and generate a relatively ordered pore structure and a relatively complete pore wall, thereby providing a favorable environment for liquid crystal generation, and thus preparing a liquid crystal polyimide aerogel; the aerogel utilizes the microscopic order of liquid crystal molecules to moderately improve the intrinsic thermal conductivity of the polyimide aerogel, and to a certain extent alleviates the contradiction of slow response rate caused by slow heat transfer in the polyimide aerogel skeleton, thereby preparing a shape memory polyimide aerogel with a fast response time, and expanding the application of polyimide aerogel in the field of intelligent deformation materials;

[0042] (3) The heat curing agent added in the present invention cross-links and solidifies the molecular chains of the polyimide aerogel during the high-temperature treatment process, which is beneficial to retaining part of the liquid crystal structure and improving the thermal conductivity; on the other hand, the chemical cross-linking structure generated by heat curing will improve the shape recovery ability of the polyimide aerogel to a certain extent, providing a strategy for improving the shape memory performance of the polyimide aerogel;

[0043] (4) The large amount of flexible monomers added in the present invention makes the polyimide molecular chain have better flexibility and improves its shape fixing ability to a certain extent. BRIEF DESCRIPTION OF THE DRAWINGS

[0044] Figure 1 A schematic diagram of the structure of a customized refrigeration cycle device used in the present invention;

[0045] Figure 2 The microstructure diagram of the liquid crystal polyimide aerogel prepared in Example 1 of the present invention; (a) is a cross-sectional SEM; (b) is a longitudinal section SEM;

[0046] Figure 3 DSC curves of the polyimide aerogels prepared in Example 1 and Comparative Examples 1 to 3 of the present invention during heating;

[0047] Figure 4 This is a POM image of the liquid crystal polyimide aerogel prepared in Example 1 of the present invention during the heating process;

[0048] Figure 5 This is a physical display diagram of the shape memory performance test process of the liquid crystal polyimide aerogel prepared in Example 1 of the present invention;

[0049] Figure 6 This is a diagram showing the results of quantitatively testing the shape memory performance of the liquid crystal polyimide aerogel prepared in Example 1 using a dynamic thermomechanical analyzer. DETAILED DESCRIPTION

[0050] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work belong to the scope of protection of the present invention. The following specific implementation methods further describe the present invention.

[0051] The method for determining the shape memory properties of the polyimide aerogel involved in the present invention is as follows:

[0052] The obtained polyimide aerogel was subjected to tensile shape memory performance test. The sample was tested using a dynamic thermal mechanical properties tester (DMA Q800, TA Company, USA) at a frequency of 1 Hz in the controlled strain mode.

[0053] 1. Determination of fixation rate

[0054] The shape memory behavior of aerogel under film stretching mode was tested by dynamic thermomechanical analysis technology, and the shape fixation rate of aerogel shape memory process was obtained by analyzing the test data. The calculation formula is:

[0055] Fixation rate (%) = (ε unload -ε0) / (ε load -ε0);

[0056] Among them, ε load represents the maximum strain under load, ε0 is the initial strain, and ε unload is the fixed strain after cooling and unloading.

[0057] 2. Response rate determination

[0058] The shape memory behavior of aerogel under film stretching mode was tested by dynamic thermomechanical analysis technology, and the shape recovery rate of aerogel shape memory process was obtained by analyzing the test data. The calculation formula is:

[0059] Response rate (%) = (ε unload -ε rec ) / (ε load -ε0);

[0060] Among them, ε load and ε rec represents the maximum strain and recovery strain under load, ε0 is the initial strain, ε unload is the fixed strain after cooling and unloading.

[0061] 3. Response time measurement

[0062] The shape memory recovery rate of the sample was measured by bending test. The specific experimental steps are as follows: (1) Place the sample in a g (1) Place the sample in a muffle furnace at a temperature of 20°C or above and keep it warm for 1 min; (2) Apply stress to bend the sample 180°, remove the sample from the muffle furnace, continue to apply stress at room temperature, and cool it down for 1 min; (3) Place the sample back into the muffle furnace and observe its shape recovery process. The recovery time is the time required for the sample to fully recover or recover to the maximum extent (when it cannot fully recover).

[0063] Example 1

[0064] A method for preparing a liquid crystal polyimide aerogel with excellent shape memory properties comprises the following steps:

[0065] (1) 1.4190 g of 1,3-bis(4-aminophenoxy)benzene and 1.4209 g of 1,3-bis(3-aminophenoxy)benzene were dissolved in 38.51 ml of N-methylpyrrolidone, 4.0745 g of 4,4'-dioxyphthalic anhydride was added, and the mixture was reacted in an ice-water bath for 18 h; then 0.0718 g of 4-ethynylaniline was added, and the reaction was continued for 6 h to prepare a polyamic acid solution with a solid content of 15%; the prepared polyamic acid solution was precipitated with ultrapure water, and then frozen in a -80°C freezer for 2 h, and then dried in a -80°C freezer for 72 h to obtain polyamic acid dry silk;

[0066] (2) dissolving 1.1 g of the polyamic acid dry silk obtained in step (1) in 10 ml of ultrapure water, adding 0.32 g of triethylamine to accelerate the dissolution, and stirring evenly at 38° C. to obtain a polyamic acid aqueous solution, wherein the polyamic acid concentration is 110 mg / ml;

[0067] (3) The polyamic acid aqueous solution obtained in step (2) was injected into a silica gel mold, and then the mold was placed in a custom-made refrigeration cycle device (such as a -80°C refrigeration cycle device) with a copper plate on top. Figure 1 ) and freeze-dried for 3 h, and then placed in a freeze dryer at -80 °C for 72 h to obtain a polyamic acid aerogel;

[0068] (4) The polyamic acid aerogel obtained in step (3) is placed in a tubular furnace, and the polyamic acid is imidized and thermally cured at high temperature in a nitrogen atmosphere. The high temperature treatment temperature program is 100° C. for 1 h, 200° C. for 1 h, and 300° C. for 1 h. Finally, a liquid crystal polyimide aerogel with excellent shape memory properties is obtained, which is recorded as PIA-RM1.

[0069] Example 2

[0070] The only difference from Example 1 is that the polyamic acid concentration in step (2) is adjusted to 70 mg / ml, the mass of the polyamic acid dry silk is 0.7 g, and the amount of triethylamine added is 0.20 g; other conditions and parameters are the same as those in Example 1.

[0071] The properties of the obtained liquid crystal polyimide aerogel were measured, and it was found that the aerogel had defects such as surface cracks due to low solid content and poor morphology.

[0072] Example 3

[0073] The only difference from Example 1 is that the polyamic acid concentration in step (2) is adjusted to 150 mg / ml, the mass of the polyamic acid dry silk is 1.5 g, and the amount of triethylamine added is 0.75 g; other conditions and parameters are the same as those in Example 1.

[0074] The properties of the obtained liquid crystal polyimide aerogel were measured, and it was found that the aerogel had a very poor formability and had defects such as foaming and irregular growth due to the high solid content and difficulty in removing bubbles during the preparation process.

[0075] Comparative Example 1

[0076] The only difference from Example 1 is that after the polyamic acid aqueous solution prepared in step (3) is poured into the silica gel mold, the mold is directly placed in a -80°C freezer for normal freezing (non-directional), and the other conditions and parameters are the same as those in Example 1. The obtained polyimide aerogel is recorded as PIA-RMNO.

[0077] Comparative Example 2

[0078] The only difference from Example 1 is that no thermal curing agent 4-ethynylaniline is added in the reaction of step (1), and other conditions and parameters are the same as those of Example 1. The obtained polyimide aerogel is recorded as PIA-RM2.

[0079] Comparative Example 3

[0080] The only difference from Example 1 is that the diamine added in the adjustment step (1) is 1.9439 g of 4,4'-diaminodiphenyl ether (the amount of substance is the same as the total amount of diamine in Example 1), and the dianhydride added is 2.9798 g of 3,3',4,4'-biphenyltetracarboxylic dianhydride (the amount of substance is the same as the amount of dianhydride in Example 1). Other conditions and parameters are the same as those in Example 1. The obtained polyimide aerogel is recorded as PIA.

[0081] Performance measurement

[0082] 1. Liquid crystal polyimide aerogel structure characterization

[0083] Figure 2 This is a SEM electron microscope image of the surface of the liquid crystal polyimide aerogel prepared in Example 1. Figure 2 As shown, the interior of the liquid crystal polyimide aerogel has a relatively ordered pore structure and relatively complete pore walls, which are conducive to the growth of liquid crystals.

[0084] 2. Characterization of Liquid Crystalline Polyimide Aerogel Liquid Crystal Structure

[0085] Figure 3 The DSC curves of the liquid crystal polyimide aerogel prepared in Example 1 and the polyimide aerogel prepared in Comparative Example 1 during the heating process are shown in FIG. Figure 3 It can be seen that during the heating process, Example 1 shows a complete endothermic peak (peak at about 300°C), which is attributed to the gradual transformation of Example 1 from an amorphous phase to a liquid crystal phase; Figure 4 The POM image of Example 1 shows that bright areas (concentric circle diffraction phenomenon) begin to appear in the field of view at 300°C. This is because Example 1 has entered the liquid crystal generation temperature range.

[0086] And in Figure 3 It can be seen that comparative example 1 only has a glass transition process (about 192°C), and there is no obvious transition process from amorphous phase to liquid crystal phase. This is attributed to the fact that comparative example 1 has not been directional frozen to generate an ordered pore structure and a complete pore wall, and the growth of the liquid crystal structure is difficult; it proves that comparative example 1 without directional freezing has no liquid crystal phase generated (or very little liquid crystal structure) during the heating process; comparative example 2 has thermotropic liquid crystal behavior and an endothermic peak of liquid crystal transition (peak at 280°C), but compared with example 1, no thermal curing agent is added, so its liquid crystal structure cannot be cured and retained; comparative example 3 synthesizes non-liquid crystal polyimide, and only has a glass transition process.

[0087] 2. Determination of thermal conductivity of liquid crystal polyimide aerogel

[0088] The thermal conductivity of the liquid crystal polyimide aerogels prepared in Example 1 and Comparative Examples 1 to 3 was measured multiple times, and the results are shown in Table 1:

[0089] Table 1. Thermal conductivity determination

[0090] <![CDATA[Temperature ( o °C)]]> <![CDATA[Thermal conductivity (W m -1 K -1 )]]> Example 1 25 0.0953 Comparative Example 1 25 0.0646 Comparative Example 2 25 0.0769 Comparative Example 3 25 0.0631 Example 1 250 0.1174 Comparative Example 1 250 0.0878 Comparative Example 2 250 0.0982 Comparative Example 3 250 0.0775

[0091] At present, due to the low density and high porosity of aerogel, its thermal conductivity is generally low (the thermal conductivity is usually 0.01-0.05Wm -1 K -1). As can be seen from Table 1, the liquid crystal polyimide aerogel prepared in Example 1 has a relatively high thermal conductivity. At the same time, it can be found that the thermal conductivity increases with the increase of temperature, which is expected to achieve the shape memory rapid thermal response of polyimide aerogel at high temperature; while the aerogel prepared in Comparative Example 1 has not been subjected to directional freezing casting, the internal pore structure of the aerogel is disordered and the pore wall is missing, the liquid crystal growth is difficult, and it is difficult to form a good thermal conduction path; since no thermal curing agent is added to Comparative Example 2, the liquid crystal structure is retained less or even not, so the thermal conductivity is relatively low; Comparative Example 3 is not a liquid crystal polyimide aerogel, so even directional freezing cannot significantly improve its thermal conductivity.

[0092] 3. Determination of shape memory properties of liquid crystal polyimide aerogel

[0093] Table 2. Shape memory properties of liquid crystal polyimide aerogels

[0094]

[0095]

[0096] As can be seen from Table 2, the fixation rate of Comparative Example 1 is lower and the recovery rate is slightly higher. The reason is that the molecular chain of Comparative Example 1 is more disordered than that of Example 1, with more physical entanglement points and relatively weaker fixation ability. In general, the shape memory performance of Example 1 and Comparative Example 1 is not much different, and the shape fixation rate and recovery rate are both higher than 97%, both of which have excellent shape memory performance. Comparative Example 2 has no chemical crosslinking points generated by curing, resulting in weaker shape recovery energy, and Comparative Example 3 has weaker shape fixation ability due to the overly hard chain segments. In terms of recovery time, Example 1 has the fastest recovery time, while Comparative Example 1 is relatively weak. The reason is that the shape recovery ability of Example 1 and Comparative Example 1 is almost the same, but the thermal conductivity of Example 1 is significantly higher than that of Comparative Example 1, which can reach the transition temperature faster and thus achieve shape recovery faster.

[0097] from Figure 5 The shape memory physical display diagram of Example 1 shows that Example 1 has a rapid thermal response during the shape recovery process. Figure 6 In the thermodynamic curve diagram of multiple shape memory cycles of Example 1, it is found that the thermodynamic curves of multiple cycles almost completely overlap, indicating that its shape memory performance is very stable and excellent.

[0098] The embodiments provided above are not intended to limit the scope of the present invention, and the steps described are not intended to limit the execution order thereof. Those skilled in the art may make obvious improvements to the present invention in combination with existing common knowledge, which also fall within the scope of protection defined by the claims of the present invention.

Claims

1. A liquid crystal polyimide aerogel with excellent shape memory properties, characterized in that: The shape fixation rate of the liquid crystal polyimide aerogel is ≥99%, the shape recovery rate is ≥97%; the thermal conductivity at room temperature is ≥0.09 W m -1 K -1 .

2. A method for preparing a liquid crystal polyimide aerogel with excellent shape memory properties, characterized in that: The method comprises the following steps: (1) subjecting a liquid crystal diamine, a flexible diamine monomer and a liquid crystal dianhydride monomer to a condensation polymerization reaction in N-methylpyrrolidone, adding a thermal curing agent after the reaction, and continuing the reaction to obtain a polyamic acid solution; subjecting the polyamic acid solution to solvent replacement, and then freezing and freeze-drying to obtain polyamic acid dry fibers; The liquid crystal dianhydride monomer is 4,4'-phenylenedioxydiphthalic anhydride; (2) adding the polyamic acid dry silk obtained in step (1) and triethylamine into ultrapure water, heating and stirring evenly to obtain a polyamic acid aqueous solution; (3) injecting the polyamic acid aqueous solution obtained in step (2) into a silica gel mold, and placing the mold on a customized refrigeration cycle device with a copper plate on the top for directional freeze casting, and placing it in a freeze dryer for freeze drying after molding to obtain a polyamic acid aerogel; (4) The polyamic acid aerogel obtained in step (3) is subjected to thermal imidization and thermal curing to obtain a liquid crystal polyimide aerogel, that is, a liquid crystal polyimide aerogel with excellent shape memory properties.

3. The method according to claim 2, characterized in that The liquid crystal diamine monomer in step (1) is one or both of 1,3-bis(4-aminophenoxy)benzene and 1,4-bis(4-aminophenoxy)benzene.

4. The method according to claim 2, characterized in that: The flexible diamine monomer in step (1) is 1,3-bis(3-aminophenoxy)benzene.

5. The method according to claim 2, characterized in that: The heat curing machine in step (1) is one or two of 4-ethynylaniline and nadic anhydride.

6. The method according to claim 2, characterized in that In step (1), the molar ratio of the liquid crystal diamine monomer to the flexible diamine monomer is 1:(0-1), and the molar ratio of the liquid crystal diamine monomer to the liquid crystal dianhydride monomer is 1:(0.95-2.5).

7. The method according to claim 2, characterized in that The molar ratio of the liquid crystal diamine to the thermal curing agent in step (1) is 1:(0-0.1).

8. The method according to claim 2, characterized in that: The concentration of polyamic acid in the polyamic acid aqueous solution in step (2) is 100-120 mg / ml.

9. The method according to claim 2, characterized in that: The temperature of the directional freeze casting in step (3) is -120 to -20°C, and the time is 1 to 24 hours.

10. Application of the liquid crystal polyimide aerogel with excellent shape memory properties as claimed in claim 1 or the liquid crystal polyimide aerogel prepared by the preparation method according to any one of claims 2 to 9 in thermal insulation materials, aerospace vehicles, deployable panels, and lightweight intelligent deformation materials.

Citation Information

Patent Citations

  • Intrinsic high-thermal-conductivity liquid crystal polyimide film and preparation method thereof

    CN113105658A

  • Shape memory polyimide molding powder, preparation method and application thereof, and shape memory polyimide three-dimensional block material

    CN116041702A

  • Shape memory polyimide aerogel and preparation method thereof

    CN116082836A

  • Liquid crystal polyimide aerogel with thermotropic liquid crystal behavior and preparation method thereof

    CN119529370A

  • Polyimide aerogels with reduced shrinkage from isothermal aging

    US10723857B1

Cited By

  • Liquid crystal polyimide aerogel with thermotropic liquid crystal behavior and preparation method thereof

    CN119529370A

  • A liquid crystal polyimide aerogel with thermotropic liquid crystal behavior and its preparation method

    CN119529370B

  • Flexible oriented nanopore organic semiconductor aerogel as well as preparation method and application thereof

    CN120904521A

  • A flexible oriented nanoporous organic semiconductor aerogel, its preparation method and application

    CN120904521B